Novel self-similar re-entrant auxetic metamaterials (SREAM): Design, mechanical property, and geometric optimization - Peng Dong; Runsheng Hou; Jiayi Hu; Chen Lin; Yuqing Liu; Lei Qin (Polymer Testing, 2023)
In this study, a novel self-similar re-entrant auxetic metamaterial (SREAM) was designed to improve its mechanical performance compared with the conventional re-entrant structure (CRS). Experimental and numerical analyses were carried out to investigate their mechanical performance under quasi-static compression. The mechanical effects of key geometric parameters of inner re-entrants have also been symmetrically investigated to provide the modeling basis for SREAMs’ geometric optimization. It was found that SREAM do well in both stiffness and auxeticity simultaneously. The mechanical performance of SREAMs is highly adjustable via proper configuration on geometric parameters. The proposed SREAM possibly provides superior auxeticity and high stiffness, with adjustable performance.